Correlation of enhanced electrical properties and domain structure of high-TC PMN-PH-PT ceramics prepared by different methods. Issue 9 (15th June 2018) - Zhu, Rongfeng; Zhang, Qihui; Fang, Bijun; Wu, Dun; Zhao, Xiangyong; Ding, Jianning
Abstract: The dielectric, ferroelectric and piezoelectric properties of the high-Curie temperature (high-TC ) 0.15Pb(Mg1/3 Nb2/3 )O3 -0.38PbHfO3 -0.47PbTiO3 (0.15PMN-0.38PH-0.47PT) ceramics synthesized by three different methods were investigated. The 0.15PMN-0.38PH-0.47PT ceramics prepared by the partial oxalate route present the best electrical properties (TC = 291 °C, εm = 28, 937, Pr = 32.89 μC/cm 2, Ec = 9.35 kV/cm, d33 = 456.2 pC/N and Kp = 67.2%) and excellent thermal stability of the piezoactivity properties under TC . Piezoresponse force microscopy (PFM) and confocal Raman microscopy (CRM) were employed to probe the nanoscale mechanism responsible for the performance difference of the 0.15PMN-0.38PH-0.47PT ceramics prepared by three different methods, disclosing the existence of the fine stripe domains, which make up the big island domains. The interplay between the macroscopic properties and nanoscopic domain structures of the 0.15PMN-0.38PH-0.47PT ceramics has been revealed. The better ferroelectric and piezoelectric response arise from the smaller domain size, which reduces the domain wall energy; whereas the higher coercive field Ec detected by the polarization-electric field (P-E) loops results from the harder domain switching for the 0.15PMN-0.38PH-0.47PT ceramics prepared by the wet chemical synthesis techniques.